HOW STRONGLY DOES MILITARY EXPENDITURE IMPACT ECONOMIC GROWTH AND THE EXCHANGE RATE? Empirical Study in Indonesia Using Time Series Data 1999-2021 - Soelistyo, Aris (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
One of the fiscal policy strategies used by the government to strengthen the economy and national security is military expenditure. There are many inconsistencies in the results of research examining the influence of military expenditure on economic growth, and it is still rare to find research that validates the influence of military expenditure on the exchange rate. Through time series data in Indonesia during the 1999-2021 period, this research validates the relationship between these three variables using Two-stage Least Square (2SLS) Regression Analysis. The estimation results using econometric models provide empirical evidence of the strength of military expenditure in influencing economic growth and the exchange rate, although the level of influence on economic growth is much higher than the exchange rate. It is recommended that further research carry out a Granger causality test and a Johansen cointegration test to determine the term of the causal relationship between the three variables studied.